Targeting hyperactivation of the AKT survival pathway to overcome therapy resistance of melanoma brain metastases. (12th December 2012) - Niessner, Heike; Forschner, Andrea; Klumpp, Bernhard; Honegger, Jürgen B.; Witte, Maria; Bornemann, Antje; Dummer, Reinhard; Adam, Annemarie; Bauer, Jürgen; Tabatabai, Ghazaleh; Flaherty, Keith; Sinnberg, Tobias; et al.
Abstract Brain metastases are the most common cause of death in patients with metastatic melanoma, and the RAF‐MEK‐ERK and PI3K‐AKT signaling pathways are key players in melanoma progression and drug resistance. The BRAF inhibitor vemurafenib significantly improved overall survival. However, brain metastases still limit the effectiveness of this therapy. In a series of patients, we observed that treatment with vemurafenib resulted in substantial regression of extracerebral metastases, but brain metastases developed. This study aimed to identify factors that contribute to treatment resistance in brain metastases. Matched brain and extracerebral metastases from melanoma patients had identical ERK, p‐ERK, and AKT immunohistochemistry staining patterns, but there was hyperactivation of AKT (p‐AKT) and loss of PTEN expression in the brain metastases. Mutation analysis revealed no differences in BRAF, NRAS, or KIT mutation status in matched brain and extracerebral metastases. In contrast, AKT, p‐AKT, and PTEN expression was identical in monolayer cultures derived from melanoma brain and extracerebral metastases. Furthermore, melanoma cells stimulated by astrocyte‐conditioned medium showed higher AKT activation and invasiveness than melanoma cells stimulated by fibroblast‐conditioned medium. Inhibition of PI3K‐AKT signaling resensitized melanoma cells isolated from a vemurafenib‐resistant brain metastasis to vemurafenib. Brain‐derived factors appear to induce hyperactivation of the AKT survival pathway and to promote the survival and drug resistance of melanoma cells in the brain. Thus, inhibition of PI3K‐AKT signaling shows potential for enhancing and/or prolonging the antitumor effect of BRAF inhibitors or other anticancer agents in melanoma brain metastases.